Lipofection of plasmid DNA into human mast cell lines using lipid nanoparticles generated by microfluidic mixing. Issue 3 (18th April 2018) - Duguay, Brett A; Huang, Kate Wei-Chen; Kulka, Marianna
Abstract: Mast cells are important immune cells that have significant roles in mediating allergy and asthma. Therefore, studying the molecular mechanisms regulating these and other processes in mast cells is important to elucidate. Methods such as lipofection, transduction, and electroporation are often employed to dissect these mechanisms by disrupting gene expression in mast cell lines. However, as with other leukocytes, human mast cells (HMCs) are often refractory to the delivery of plasmids by lipofection. In this study, we investigated the utility of lipid nanoparticles (LNPs) containing the ionizable cationic lipids 1, 2-dioleoyloxy-3-dimethylaminopropane, 1, 2-dioleyloxy-3-dimethylaminopropane, or 2, 2-dilinoleyl-4-(2-dimethylaminoethyl)-[1, 3]-dioxolane for the delivery of plasmid DNA into HMC lines. Herein, we demonstrate for the first time the use of LNPs to achieve significant and reproducible levels of plasmid DNA transfection in HMC-1.2 and laboratory of allergic diseases 2 (LAD2) cells. These levels reached 53.2% and 16.0% in HMC-1.2 and LAD2 cells, respectively; and outperformed Lipofectamine 3000 in both cases. Moreover, cell viability in the transfected cells remained above 65% for all LNP conditions tested. Together, these observations illustrate the efficacy of this technique for mast cell researchers and further support the use of LNPs for nucleic acid delivery into leukocytes. Method based on DNA-lipid nanoparticles successfully and reproducibly transfects human mast cell lines while yielding levels of transgene expression and cell viability superior to traditional lipofection techniques.